Viscoelastic impact characterisation of solid sports balls used in the Irish sport of Hurling - Collins, Fiachra; Brabazon, Dermot; Moran, Kieran (Sports Engineering, 2011)
In recent years, variability in behaviour of the sliotar, a small leather-bound ball used in the Irish sport of hurling, has become evident in championship matches. The inconsistency in performance was attributed to the range of constructions and material compositions of currently approved ball types. With a view to adopting a standard core, a new methodology has been commissioned to assess the dynamic impact behaviour of approved sliotar cores. In this paper, the relationship between the dynamic stiffness and the coefﬁcient of restitution is presented with regard to material properties, ball construction and viscoelastic strain and strain-rate dependencies. The modern polymer ball types were shown to exhibit strain-rate sensitivity, while the performance of the traditional multi-compositional ball types exhibited lesser strain-rate dependence. The traditional balls types were shown to be up to 2.5 times stiffer than the modern ball types, with this ﬁnding having implications for ball energy dissipation.
Keywords: Ball types; compression (voyant); deformation; impact; stifness